2003
DOI: 10.1111/1467-9507.00248
|View full text |Cite
|
Sign up to set email alerts
|

Relational Aggression, Relational Victimization, and Language Development in Preschoolers

Abstract: We investigated language development, relational aggression, and relational victimization in ethnically, socioeconomically diverse preschoolers. Relational aggression was positively related to language development. Girls were more relationally aggressive than boys, and higher-socioeconomic status (SES) children were more relationally aggressive and victimized than lower-SES children. Neither gender nor SES conclusively moderated the relation between language and relational aggression, though some findings sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
101
1
11

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(123 citation statements)
references
References 52 publications
10
101
1
11
Order By: Relevance
“…In our study if the violence is occurring within family, mostly the male children are affected and express aggression after physical battering and abuses of parents. This study also showed that female children were affected in 40.7% cases compared to other studies [21][22][23].…”
Section: Discussionsupporting
confidence: 73%
“…In our study if the violence is occurring within family, mostly the male children are affected and express aggression after physical battering and abuses of parents. This study also showed that female children were affected in 40.7% cases compared to other studies [21][22][23].…”
Section: Discussionsupporting
confidence: 73%
“…Enfin, en ce qui a trait aux facteurs de risque familiaux distaux, nous n'avons pas observé que les filles indirectement agressives provenaient de milieux plus défavorisés que les filles comparativement aux filles non agressives (Bonica et al, 2003). Il est possible que notre échantillon, essentiellement recruté dans des écoles de quartiers défavorisés, ait amoindri ces différences.…”
Section: Discussionunclassified
“…Si, par leur nature, les conduites d'agression indirecte passent souvent inaperçues, les effets de ce mode d'agression peuvent être percutants. Pour plusieurs victimes, en effet, la souffrance et l'humiliation engendrées par l'agression indirecte ne sont pas épisodiques et peuvent persister au fil des années : la victime n'a pas seulement à composer avec des ragots et des mensonges, mais aussi avec l'isolement, la solitude et le rejet (Underwood, 2003 (Bonica et al, 2003), alors que tantôt aucun lien significatif n'est constaté entre ces deux variables (Doyle et al, 2004). Ces résultats contradictoires soulignent, à l'évidence, la nécessité de poursuivre les recherches sur les facteurs de risque sociaux, familiaux et comportementaux liés aux conduites d'agression indirecte des filles.…”
Section: Groupe De Recherche Sur Les Inadaptations Sociales De L'enfaunclassified
“…관계적 공격성은 또 래 관계나 사회적 소속감을 손상시키거나 조종하는 것에 의하여 다른 사람에게 의도적인 해를 입히는 것으로 정 의된다 (Crick & Grotpeter, 1995). 초기 공격성 연구는 외현적 공격성에 집중되어 남성이 여성보다 공격적이라 는 견해가 일반화되었지만, 이후에 다른 유형의 공격성 즉 관계적 공격성을 함께 비교한 연구에서는 여성이 남 성보다 관계적 공격성 수준이 높은 것으로 나타났다 (Bonica et al, 2003;Crick & Grotpeter, 1995). 이러 한 공격성 연구의 흐름 속에서 Little et al(2003) Bonica et al, 2003;Ostrov et al, 2004).…”
unclassified
“…초기 공격성 연구는 외현적 공격성에 집중되어 남성이 여성보다 공격적이라 는 견해가 일반화되었지만, 이후에 다른 유형의 공격성 즉 관계적 공격성을 함께 비교한 연구에서는 여성이 남 성보다 관계적 공격성 수준이 높은 것으로 나타났다 (Bonica et al, 2003;Crick & Grotpeter, 1995). 이러 한 공격성 연구의 흐름 속에서 Little et al(2003) Bonica et al, 2003;Ostrov et al, 2004). Ostrov et al(2004) [ Eisenberg et al, 1993;Rubin et al, 1991;Stocker & Dunn, 1990 (Campbell, 1995;Hart et al, 1998;Oweus, 1991 …”
unclassified